Diagnostic value of different interleukins and procalcitonin in critically ill patients admitted with suspected sepsis - Simmi Mehra; Aseem Kumar Tiwari; Geet Aggarwal; Swati Pabbi Mehta; Rajni Chauhan; Chhavi Rajvanshi; Deepak Govil (Wolters Kluwer Medknow Publications, 2022)
Background: Many biomarkers have now been studied such as C-reactive Protein (CRP), procalcitonin (PCT), etc., and are widely used for the diagnosis of sepsis in clinical practice which may determine the appropriate antibiotic treatment. A flowcytometric cytokine bead array (CBA) assay has now been used to determine multiple interleukins (IL), simultaneously. The aim of this study was to determine the cytokine (IL2, IL4, IL6, IL10, TNFα, INFγ, and IL17) profiles of interleukins in plasma of sepsis patients by using multiplex Flowcytometric CBA array assay. Materials and Methods: A total of 99 consecutive patients admitted with the suspected sepsis were studied. PCT concentrations were measured by using the enzyme-linked fluorescent immunoassay (ELFA) technique and flow cytometry-based BD™ CBA Cytokine Kit was used to evaluate levels of 7 cytokines [IL-2, IL-4, IL-6, IL-10, Tumour Necrosis Factor (TNF), Interferon- γ (IFN-γ), and IL-17A]. Results: Microbiologically defined infection (MDI) demonstrated a positive culture report in 79/99 (79.7%) of patients. The IL6 [1873.7 (4-5000)] and IL10 [(154.7 (0-1764)] levels were significantly higher in septic patients than those in the negative MDI IL6 [901 (4-5000)] and IL10 [110.4 (4-1372)] levels. The AUROC value of IL6 [0.66 (0.53-0.79)] was found to be the highest among all followed by IL10 [0.65 (0.51-0.79)], IFNγ [0.63 (0.51-0.77)], PCT [0.61 (0.48-0.75)], and TNFα [0.55 (0.42-0.69)]. Conclusion: Our study suggests that that IL6 is substantially more economical and can reduce the investigation cost to half as compared with the procalcitonin assay.